Quantitative assessment and determinants of foveal avascular zone in healthy volunteers. Issue 5 (May 2021) - Zhou, Lijun; Wang, Fengqun; Wang, Ling; Shen, Peiyang; Cao, Yi; He, Yushen; Yan, Shigang; Kong, Xiangbin; Lu, Xiaohe
Objectives: To evaluate the foveal avascular zone (FAZ) area in healthy volunteers using optical coherence tomography angiography (OCTA) and identify factors that influence the FAZ. Methods: This single-center cross-sectional study included 526 eyes of 263 healthy volunteers who underwent macular scanning by Zeiss OCTA. A linear mixed model was used to investigate the effects of systemic factors (age, sex, blood pressure, height, and weight) and ocular factors (intraocular pressure, biometric parameters, and central macular thickness) on FAZ. Results: In total, 520 eyes of 262 healthy volunteers were included in the analysis. The mean volunteer age was 38.59 ± 22.03 years (range, 5–84 years); 124 volunteers were male (47.33%) and 138 volunteers were female (52.67%). The mean FAZ area was 0.30 ± 0.03 mm 2 (95% confidence interval [CI], 0.29–0.31 mm 2 ). Univariate analysis showed that FAZ area was associated with age (β = 0.0011), anterior chamber depth (β = −0.0513), and axial length (β = −0.0202). Multivariate analysis showed that FAZ area was negatively correlated with axial length (β = −0.0181). Conclusions: The mean FAZ area in healthy volunteers, measured using Zeiss OCTA, was 0.30 ± 0.03 mm 2 . Furthermore, FAZ area was negatively associated with axial length; this relationship should be considered in clinical practice.